DENATURATION OF LABEO ROHITHA (ROHU) ACTOMYOSIN ON FROZEN STORAGE PREVENTIVE EFFECT OF CARBOHYDRATES. - RAO, S B (Fishery Technology, 2017)
The preventive effect of sucrose and glucose on the denaturation of frozen rohuactomyosin at -20oC for 7 weeks was examined using an invitro test model. The rate of Â denaturation was followed by estimating percentage salt extractability, Cal2+ ATPase activity and the clearing response test. Sucrose and glucose showed cryoprotective action for all concentration of actomyosin. Higher actomyosin concentration was preserved better than lower concentration. Post-rigor actomyosin was preserved to a greater extent than pre-rigor actomyosin. Correlation between percentage salt extractability and enzyme activity could not be observed in all sample:-. of frozen actomyosin studied.